WDM 신호의 BER 개선을 위한 OPC의 최적 파라미터에 대한 소광비의 영향 - 이성렬; 권순녀; Lee, Seong-Real; Kweon, Soon-Nyu (한국항행학회논문지, 2007)
In this paper, we numerically induced the optimal values of optical phase conjugator (OPC) position and dispersion coefficients of fiber sections, which can improve the bit error rate (BER) and design the adaptive WDM transmission system, as a function of the extinction ratio (ER) of 10 dB and 20 dB in $16{×}40$ Gb/s WDM transmission system. It is confirmed that these optimal parameter values for effectively compensating overall WDM channels are dependence on the extinction ratio of signals as well as modulation format, transmitted channel numbers, which were investigated in previous researches. It is also confirmed that ER of 20 dB has the advantage of designing flexible WDM systems using optimal parameters than ER of 10 dB. $16{×}40$ Gb/s WDM 전송 시스템에서 비트 에러율 (BER ; bit error rate)의 효과적 보상과 융통적 WDM 전송 시스템의 설계를 위한 광 위상 공액기 (OPC ; optical phase conjugator)의 최적 위치 값과 광섬유 구간의 최적 분산 계수 값들을 10 dB와 20 dB의 소광비(ER ; extinction ratio)에 따라 도출하였다. 모든 WDM 채널들의 BER의 효과적 보상을 위한 최적 파라미터 값들은 기존 연구들에서 살펴보았던 변조 파형 형식, 전송 채널수와 마찬가지로 신호의 소광비에 의존하는 것을 확인하였다. 그리고 최적 파라미터 값들을 이용한 융통적인 WDM 시스템 설계가 ER이 10 dB인 경우보다 ER이 20 dB인 경우가 더욱 유리한 것을 확인하였다.